HR development in local government: How and why does HR strategy matter in organizational change and development? - Hans-Jürgen Bruns (Business Research, 2014)
Human resource (HR) management has been proposed as being one of the core drivers of the modernization of the public sector, in particular with reference to the changing nature of people management and "HR-public service partnerships" as an antecedent capacity of modernizing public service organizations. Notwithstanding the ongoing interest in the transformation of HR systems, this study explores how and why such relationships between HR management (HRM) and organizational change emerge. Considering a resource and capability-based approach, the analysis reveals strategic HRM practices as a useful concept to distinguish HR activities and the processes that are occurring when a HR strategy is performed. Moreover, using a multiple case study design, the study exhibits the antecedents and effects of HR strategy formation during accounting change in six German local governments. The results provide evidence that forces of either strategic or administrative patterns of alignment refer to different layers and the sequencing of HRM activities within a process of HR system change, thereby revealing the possibility of contradictory effects induced by HR change agency on either the "HR" or the "public service" side of the strategic coin.
Keywords: H70; M12; M41; M53; 330; Organizational change; Human resource strategy; Multiple case study design; Resource and capability-based view